Evaluation of oxidant stress in Wilson’s disease and non-Wilsonian chronic liver disease in childhood - Buket DALGIÇ; Nesrin SÖNMEZ; Gürsel BİBEROĞLU and Alev HASANOĞLU and Deniz ERBAŞ (Turkish Journal of Gastroenterology, 2019)
-